Effect of Therapeutic Drug Monitoring and Cytochrome P450 2C19 Genotyping on Clinical Outcomes of Voriconazole: A Systematic Review. Issue 4 (April 2021) - Lee, Joseph; Ng, Patrick; Hamandi, Bassem; Husain, Shahid; Lefebvre, Melissa J.; Battistella, Marisa
Objectives: To examine current knowledge on the clinical utility of therapeutic drug monitoring (TDM) in voriconazole therapy, the impact of CYP2C19 genotype on voriconazole plasma concentrations, and the role of CYP2C19 genotyping in voriconazole therapy. Data Sources: Three literature searches were conducted for original reports on (1) TDM and voriconazole outcomes and (2) voriconazole and CYP2C19 polymorphisms. Searches were conducted through EMBASE, MEDLINE/PubMed, Scopus, and Cochrane Central Register of Controlled Trials from inception to June 2020. Study Selection and Data Extraction: Randomized controlled trials, cohort studies, and case series with ≥10 patients were included. Only full-text references in English were eligible. Data Synthesis: A total of 63 studies were reviewed. TDM was recommended because of established concentration and efficacy/toxicity relationships. Voriconazole trough concentrations ≥1.0 mg/L were associated with treatment success; supratherapeutic concentrations were associated with increased neurotoxicity; and hepatotoxicity associations were more prevalent in Asian populations. CYP2C19 polymorphisms significantly affect voriconazole metabolism, but no relationship with efficacy/safety were found. Genotype-guided dosing with TDM was reported to increase chances of achieving therapeutic range. Relevance to Patient Care and Clinical Practice: Genotype-guided dosing with TDM is a potential solution to optimizing voriconazole efficacy while avoiding treatment failures and common toxicities. Conclusions: Voriconazole plasma concentrations and TDM are treatment outcome predictors, but research is needed to form a consensus target therapeutic range and dosage adjustment guidelines based on plasma concentrations. CYP2C19 polymorphisms are a predictor of voriconazole concentrations and metabolism, but clinical implications are not established. Large-scale, high-methodological-quality trials are required to investigate the role for prospective genotyping and establish CYP2C19 -guided voriconazole dosing recommendations.